THE ROLE AND EFFECTIVENESS OF INTERNATIONAL ORGANIZATIONS IN COMBATING HUMAN TRAFFICKING - Jumaniyozova Zarnigor Makhammadi kizi (PT. Antis International Publisher, 2026)
Objective: Human trafficking remains one of the most serious transnational crimes threatening human rights, human dignity, and international security. This article analyzes the role and effectiveness of international organizations in combating human trafficking through international cooperation, legal regulation, victim protection, and preventive measures. The research focuses on the activities of major international organizations, including the United Nations, International Organization for Migration, Organization for Security and Co-operation in Europe, and International Labour Organization. Their contribution to strengthening international legal standards, coordinating cross-border cooperation, and supporting victims of trafficking is examined in detail. Method: Using comparative legal analysis and international experience, the article identifies effective mechanisms used in different countries and international institutions. The article also evaluates international legal instruments aimed at preventing trafficking in persons and prosecuting offenders. Particular attention is paid to the implementation of international conventions and protocols in national legislation and the challenges faced by states in practice. Results: The study highlights existing problems such as insufficient international coordination, difficulties in identifying victims, lack of financial resources, and the growing use of digital technologies by trafficking networks. The findings demonstrate that effective cooperation between states and international organizations is essential for reducing human trafficking and ensuring the protection of fundamental human rights at the global level. Novelty: Furthermore, the research proposes several recommendations for improving international cooperation, enhancing legal frameworks, strengthening victim protection systems, and increasing the efficiency of anti-trafficking policies.